Relationship between iron deficiency anemia and febrile seizures in children: A systematic review and meta-analysis. (November 2017) - Kwak, Byung Ok; Kim, Kyungmin; Kim, Soo-Nyung; Lee, Ran
Highlights: The association between iron deficiency anemia (IDA) and febrile seizures (FS) is inconclusive. We performed a meta-analysis to determine an association between IDA and FS. This meta-analysis suggests that IDA is associated with an increased risk of FS in children. Abstract: Purpose: The association between iron deficiency anemia (IDA) and febrile seizures (FS) during childhood is inconclusive due to inconsistent results reported in different studies. We performed a systematic review and meta-analysis to determine an association between IDA and FS in children. Methods: We searched PubMed, EMBASE, and Cochrane Library databases for studies published up to August 2015 using the following key words: ["iron deficiency" OR "iron status"] AND ["febrile seizure" OR "febrile convulsion"] AND ["pediatric" OR "infant" OR "child"]. Pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using standard meta-analysis techniques. Subgroup analysis also was performed. Results: A total of 17 studies enrolling 2416 children with FS and 2387 controls were included in the meta-analysis. The results indicated that IDA was significantly associated with FS (OR, 1.98; 95% CI, 1.26–3.13; P  = 0.003). Subgroup analyses evaluated the diagnostic indices for IDA including serum iron, plasma ferritin, and mean corpuscular volume (MCV). The results indicated that IDA diagnosed on the basis of plasma ferritin (OR, 3.78; 95% CI, 1.80–7.94; P  < 0.001) or MCV (OR, 2.08; 95% CI, 1.36–3.17; P  = 0.001) was modestly associated with FS, whereas IDA diagnosed on the basis of two serum iron studies was not associated with FS (OR, 0.57; 95% CI, 0.24–1.37; P  = 0.210). Conclusion: The results of this meta-analysis suggest that IDA is associated with an increased risk of FS in children.